(untitled) (International Journal of Engineering and Computer Science, 2017)
The design of secure authentication protocols is quite difficult, considering that varied types of root kits reside in PC’s (Personal Computers) to look at user’s behavior and to create PCs un-trusted devices. Involving human in authentication protocols, whereas promising, isn’t straightforward because of their restricted capability of computation and acquisition. Therefore, wishing on users to reinforce security necessarily degrades the usability. On the opposite hand, quiet assumptions and rigorous security style to enhance the user expertise will cause security breaches that may harm the users trust. In this paper, we tend to demonstrate however careful visualization style will enhance not solely the safety however conjointly the usability of authentication. thereto finish, we tend to propose two visual authentication protocols: one may be a one-time-password protocol, and therefore the alternative may be a password-based authentication protocol. Through rigorous analysis, we tend to verify that our protocols area unit proof against several of the difficult authentication attacks applicable within the literature. what is more, mistreatment an in depth case study on a epitome of our protocols, we tend to highlight the potential of our approach for real-world deployment: we tend to were able to win a high level of usability whereas satisfying rigorous security necessities.